Azilsartan Medoxomil, an Angiotensin II Receptor Antagonist for the Treatment of Hypertension. Issue 4 (19th June 2017) - Hjermitslev, Marie; Grimm, Daniela G.; Wehland, Markus; Simonsen, Ulf; Krüger, Marcus
Abstract: Azilsartan (AZL) medoxomil was approved by the United States Food and Drug Administration in 2011 for the treatment of hypertension and has shown promising results both in blood pressure (BP) reduction and in tolerability, but has not yet been taken into practice to the same extent as other angiotensin II receptor blockers (ARBs) that have been on the market for a longer period. AZL antagonizes the AT1 receptor for angiotensin II (ANG II), whereas angiotensin‐converting enzyme inhibitors block the conversion of angiotensin I to ANG II, but not alternative routes of formation of ANG II. The bioavailability of AZL is about 60% and it has a t max of 1.5–3 hr and a half‐life of approximately 11 hr. With its IC50 of 7.4 nM after 5 hr of drug washout in radioligand assays, AZL has a tighter and longer‐lasting binding to the AT1 receptor by several orders of magnitude than other ARBs, which might lead to a more effective reduction in BP. Clinical studies have revealed that AZL doses of 40 and 80 mg/day reduce BP significantly better than maximal clinical doses of valsartan or olmesartan, while being well tolerated and exhibiting a spectrum of adverse effects comparable to those of other ARBs. These properties of AZL might lower the risk of cardiovascular disease and thereby reduce mortality rates. However, the existing mortality studies have not found this correlation, which should be further investigated.